Mean pulmonary arterial pressure after percutaneous mitral valvuloplasty predicts long-term adverse outcomes - Jorge, E (2012)
INTRODUCTION AND AIM: Percutaneous mitral valvuloplasty (PMV) is an effective treatment option for mitral stenosis (MS), but its success is assessed on the basis of clinical and echocardiographic outcomes in studies with relatively short follow-up. We aimed to characterize a cohort of patients undergoing PMV with long-term follow-up and to determine independent predictors of post-PMV mitral re-intervention and event-free survival. METHODS: We studied 91 consecutive patients with MS who underwent PMV with a median clinical follow-up duration of 99 months. Two endpoints were considered: post-PMV mitral re-intervention (PMV or mitral surgery) and a composite clinical events endpoint including cardiovascular death, mitral valve re-intervention and hospital admission due to decompensated heart failure. We compared patients who required post-PMV mitral re-intervention with those who did not during follow-up. RESULTS: The study population included 83.5% females and mean age was 48.9±13.9 years. The 1-, 3-, 5-, 7- and 9-year rates of clinical event-free survival were 93.0±2.8%, 86.0±3.9%, 81.0±4.4%, 70.6±5.6%, and 68.4±5.8%, respectively. The 1-, 3-, 5-, 7- and 9-year rates of mitral re-intervention-free survival were 98.8±1.2%, 97.5±1.7%, 92.1±3.1%, 85.5±4.5%, and 85.5±4.5%, respectively. The median time to mitral re-intervention was 6.2 years. Patients who required mitral re-intervention during follow-up were younger (43.3 vs. 51.2 years, p=0.04) and had higher pre- and post-PMV mitral gradient (14.9 vs. 11.5mmHg, p=0.02 and 6.4 vs. 2.1mmHg, p<0.001) and higher post-PMV mean pulmonary artery pressure (mPAP) (30.0 vs. 23.2mmHg, p=0.01). In a Cox proportional hazards model, mPAP ≥25mmHg was the sole predictor of both mitral re-intervention (HR 5.639 [1.246-25.528], p=0.025) and clinical events (HR 3.622 [1.070-12.260], p=0.039). CONCLUSION: In our population, immediate post-PMV mPAP was the sole predictor of post-PMV mitral intervention. These findings may help identify patients in need of closer post-PMV follow-up.